Are Clinicians Communicating Adequately with Radiologists through Radiological Requisition? A Clinical Audit Assessing Current Local Practice - Koirala, Aabesh; Bhandari, Shama (Nepalese Journal of Radiology, 2022)
Introduction: A radiological request form is the only communication tool between the treating physician and the radiologist. This study was conducted to assess the adequacy of filled radiological request forms in a tertiary health institute. Methods: Three hundred radiological requisition forms which were filled by doctors at the tertiary hospital were selected randomly and analyzed. The forms were evaluated for completeness of the information entered by the physician. The request forms were selected by convenience sampling method to avoid bias and included forms from multiple departments both inpatient and outpatient. Results: Our audit data revealed that out of the total 250 request forms that were analyzed only the names of the patients and the part to be examined was filled. The age and gender of the patients were filled in 99.2% and 99.6% forms respectively. A total of 59.6% of forms had provisional clinical diagnosis, name and department of the physician requesting the investigation were present in 75.6% and 66% of forms respectively. None of the forms contained the contact number of the requesting physician with 8% forms without the name of the physician and department who had filled the request form. Conclusion: At the end of our audit, we concluded that radiological request forms are rarely filled properly which results in inadequate transmission of clinical information.